Ampacity analysis of extra-high voltage XLPE submarine cable in typical layout environments - ZHANG Hao; LI Pengfei; MA Guoqing; DUAN Yubing; ZHENG Yuesheng; LI Zhonglei (电力工程技术, 2022)
The layout environments of the extra-high voltage (EHV) submarine cable are complex and changeable,and the ampacity of the EHV submarine cable varies under different layout environments. Therefore,it is essential to analyze the ampacity of the EHV submarine cable in typical layout environments. In this paper,a steady-state thermal circuit model for the alternating current (AC) 500 kV cross linked polyethylene (XLPE) EHV submarine cable based on IEC 60287 standard is established,and the influences of layout sections,layout methods,environment temperatures,and layout depths on the ampacity of EHV submarine cable are studied. The results of the steady-state thermal circuit model are verified by a multi-physical field finite element model. It is found that the landing section of the submarine cable is the bottleneck section of ampacity of the whole line. When the submarine cable in the landing section is laid by pipeline method,the ampacity is about 150 A lower than that by the direct burial layout method.The ampacity of submarine cable decreases with the environment temperature and the layout depth. The finite element calculation results verify the accuracy of the results of the steady-state thermal circuit model.